Devlet Borçlarının Yüksek Seviyesi, Gelir Dağılımındaki Bozukluğu Kalıcı Duruma Getirirken, Asayiş Suçlarında Büyük Artışlara Neden Oluyor - (:unkn) unknown (My University, 2006)
ç ve Dış borçların yüksek seviyesi, 2000 yılı sonrasında artış göstermeye devam etmiştir. Son üç yıl içinde iç borçlardaki artış %63, dış borçlardaki artış %30 dolayındadır. Devlet bu borçlanmayı sürdürebilmek için, çıkardığı devlet borçlanma senetlerinin büyük bölümünü bankalara satmaktadır. Bankalar da bunları topladıkları mevduat ile satın almakta ve mevduat sahiplerine devretmektedir. Ama bunları alan mevduat sahipleri az sayıdadır. Bu az sayıdaki kişi, vadesi geldiğinde devlet borçlanma senetlerinin faizini devletten tahsil etmektedirler. Devlet bu faizleri vergi gelirlerinden karşılamaktadır. Böylece oluşan kısır döngü, ülkenin iki önemli kaynağı olan mevduat ve vergi gelirlerinin, az sayıda kişiye tahsis edilmesi sonucunu doğurmakta, bu durum da gelir dağılımındaki dengesizliğin sürüp gitmesi ve asayiş suçlarındaki artışa neden olmaktadır.

The high rates regarding internal and external debts continued to increase after the year 2000. According to the data received in recent three years, the increase in internal debt occurred as 63% and the increase in external debt occurred as 30%. In order to pursue this situation, The State sells the great amount of governmental bonds and bills to the banks. The banks buy these bonds and bills by using the money that they collected through the deposits. Afterwards, they transfer them to the owners of the deposits. Nevertheless, the persons that buy these bonds and bills are limited in number. When the fixed term finishes, these people take the interest of these bonds and bills from the State. On the other hand, State covers these interests through tax incomes. The outcome of this vicious circle causes the assignment of the deposits and fax incomes to a few number of persons due to which the unbalanced situation regarding the income distribution continues and crimes relevant to public security increases in number.
While the High Rates of State Debt Urges the Disorder of Income Distribution,it Also Increases the Crimes Relavant to Public Security
Keywords: Tarih